Efektivitas Progressive Muscle Relaxation Therapy Terhadap Penurunan Tekanan Darah Sistolik pada Wanita Lanjut Usia dengan Hipertensi Primer - Khasanah, Dini Afriani; Herawati, Isnaini (Prosiding University Research Colloquium, 2018)
Elderly, especially women have decreased the function of one of them on the circulatory system. The occurrence of decreased elasticity of blood vessel wall is one cause of the increase in blood pressure, especially systolic blood pressure. One of the treatment efforts done is progressive muscle relaxation therapy. It aims to elicit a relaxed response to affect the systemic and pulmonary circulation in order to decrease systolic blood pressure. The purpose of this study was to investigate the effectiveness of progressive muscle relaxation therapy to decrease systolic blood pressure in elderly women with primary hypertension. The type of research used is Quasi Experimental Design with Pretest-Posttest With Control Group Design research design. The number of respondents is 19 people. The results of this study showed a decrease in systolic blood pressure of 7 mmHg in the control group and 20 mmHg in the treatment group. Indenpedent test results obtained systolic blood pressure value is p value (0.003 <0.05).